Influences of Sex and Estrogen in Arterial and Valvular Calcification - Zhang, Bin; Miller, Virginia M.; Miller, Jordan D. (Frontiers in Endocrinology, 2019)
Vascular and cardiac valvular calcification was once considered to be a degenerative and end stage product in aging cardiovascular tissues. Over the past two decades, however, a critical mass of data has shown that cardiovascular calcification can be an active and highly regulated process. While the incidence of calcification in the coronary arteries and cardiac valves is higher in men than in age-matched women, a high index of calcification associates with increased morbidity and mortality in both sexes. Despite the ubiquitous portending of poor outcomes in both sexes, our understanding of mechanisms of calcification under the dramatically different biological contexts of sex remains rudimentary. Understanding how the critical context of sex informs our understanding of mechanisms of calcification—as well as innovative strategies to target it therapeutically--is essential to advancing the fields of both cardiovascular disease and fundamental mechanisms of aging. This review will explore potential sex differences in the basic biological pathways associated with vascular and cardiac valvular tissue calcification, and potential strategies of pharmacological therapy to reduce or slow these processes.